Bioactivity-guided isolation of anticancer compounds from Euphorbia lathyris. Issue 22 (22nd October 2015) - Yang, Shanshan; Sun, Jiachen; Lu, Hong; Ma, Hong; Zhang, Yaozhou
Abstract : Bioactivity-guided isolation of anticancer compounds from Euphorbia lathyris . Abstract : Euphorbia lathyris has been known traditionally for its anticancer activity. However, for weakly polar compositions of Euphorbia lathyris, there is a lack of comprehensive chromatographic purification methods. Therefore, it is necessary to establish an efficient bioassay-guided off-line 2D HPLC method for isolation and identification of anticancer compounds from the Euphorbia lathyris ethyl acetate extract. In the present study, preparative separation in the first dimension was performed on a bare silica column to simplify the sample into fractions with good separation repeatability. Then, an amide column was taken as the second dimension to realize the rapid preparation of monomers. Structures were established by 1D and 2D NMR spectroscopy. For compound2 the absolute configuration was confirmed by X-ray single crystal diffraction spectroscopy. The compounds were evaluated for their tumor cell growth inhibitory activities on HEPG2 and A549 cells by a real-time cell-analyzer. Eventually, a total of seven compounds were isolated from the Euphorbia lathyris extract, namely Euphorbia factor L2 (1 ), Euphorbia factor L1 (2 ), glyceryl monooleate (3 ), Euphorbia factor L8 (4 ), Euphorbia factor L3 (5 ), Euphorbia factor L9 (6 ), and esculetin (7 ). Compounds2 and6 showed significant anticancer activity against A549 and HEPG2 cells. Compounds1, 3, 4 and7 were ineffective against HEPG2 cells. However, the four compounds showed significant bioactivity against A549 cells. Compound5 exhibited a good inhibition of cancer cell growth activity. As mentioned above, the bioactivity-guided off-line 2D HPLC method is extremely useful for the separation of weakly polar compounds and could lead to the discovery of more useful natural anticancer compounds.